Analisa Sifat Mekanik Komposit Serat Gelas Pada Lapisan Yang Berbeda - Setiawan, Andi Tri; Salimin, Salimin; Endriatno, Nanang (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2019)
Nowadays, fiberglass composites are widely applied to the construction that receives tension and bending loads. The purpose of this research is to know and analyze the mechanical properties of fiberglass by using different layers. In this research the manufacture of composites using hand-lay-up method. The manufacture of specimen for the tensile test refers to the standard ASTM D 638-02 and standard ASTM D 790-02 bending test. The method used in data analysis is graph data analysis to see the relationship between interconnected parameters and dependence on the size of the specimen 13 mm and the number of variations in the composition of the specimen mixture. The results showed that the composition of the mixture with the highest tensile voltage of 60.2719 N/mm2 was in the variation of 5 layers and the bending test with a value of 116.93 N/mm2. While the lowest tensile strength is 33.2882 N/mm2 and the lowest bending of 100.84 N/mm2 is found in the composition of variation 2 layers.Keywords: composite, fiberglass, polyester resin